Low-frequency and common genetic variation in ischemic stroke: The METASTROKE collaboration. (29th March 2016) - Malik, Rainer; Traylor, Matthew; Pulit, Sara L.; Bevan, Steve; Hopewell, Jemma C.; Holliday, Elizabeth G.; Zhao, Wei; Abrantes, Patricia; Amouyel, Philippe; Attia, John R.; Battey, Thomas W.K.; Berger, Klaus; et al.
Abstract : Objective: To investigate the influence of common and low-frequency genetic variants on the risk of ischemic stroke (all IS) and etiologic stroke subtypes. Methods: We meta-analyzed 12 individual genome-wide association studies comprising 10, 307 cases and 19, 326 controls imputed to the 1000 Genomes (1 KG) phase I reference panel. We selected variants showing the highest degree of association ( p < 1E-5) in the discovery phase for replication in Caucasian (13, 435 cases and 29, 269 controls) and South Asian (2, 385 cases and 5, 193 controls) samples followed by a transethnic meta-analysis. We further investigated the p value distribution for different bins of allele frequencies for all IS and stroke subtypes. Results: We showed genome-wide significance for 4 loci: ABO for all IS, HDAC9 for large vessel disease (LVD), and both PITX2 and ZFHX3 for cardioembolic stroke (CE). We further refined the association peaks for ABO and PITX2 . Analyzing different allele frequency bins, we showed significant enrichment in low-frequency variants (allele frequency <5%) for both LVD and small vessel disease, and an enrichment of higher frequency variants (allele frequency 10% and 30%) for CE (all p < 1E-5). Conclusions: Our findings suggest that the missing heritability in IS subtypes can in part be attributed to low-frequency and rare variants. Larger sample sizes are needed to identify the variants associated with all IS and stroke subtypes.